Hydropower Sector of Kyrgyzstan in the Context of Solving the Water– Energy Problems in the Central Asia - B. N. Mubarakshin (Vestnik MGIMO-Universiteta, 2013)
The Kyrgyz Republic is referred to the countries with sizeable water resources. In spite of an enormous hydropower potential of the republic’s rivers the national energy sector strongly depends on the Toktogul dam’s functioning, which is also important to maintain water–energy balance in the Central Asia. In conditions of unremitting quarrelling over working regimes of this station construction of the Kambarata hydropower stations in Kyrgyzstan can be considered as one of the most optimal ways to solve regional water– energy problems.